Young and undamaged recombinant albumin alleviates T2DM by improving hepatic glycolysis through EGFR and protecting islet β cells in mice - Hongyi Liu; Anji Ju; Xuan Dong; Zongrui Luo; Jiaze Tang; Boyuan Ma; Yan Fu; Yongzhang Luo (Journal of Translational Medicine, 2023)
Abstract Background Albumin is the most abundant protein in serum and serves as a transporter of free fatty acids (FFA) in blood vessels. In type 2 diabetes mellitus (T2DM) patients, the reduced serum albumin level is a risk factor for T2DM development and progression, although this conclusion is controversial. Moreover, there is no study on the effects and mechanisms of albumin administration to relieve T2DM. We examined whether the administration of young and undamaged recombinant albumin can alleviate T2DM in mice. Methods The serum albumin levels and metabolic phenotypes including fasting blood glucose, glucose tolerance tests, and glucose-stimulated insulin secretion were studied in db/db mice or diet-induced obesity mice treated with saline or young, undamaged, and ultrapure rMSA. Apoptosis assays were performed at tissue and cell levels to determine the function of rMSA on islet β cell protection. Metabolic flux and glucose uptake assays were employed to investigate metabolic changes in saline-treated or rMSA-treated mouse hepatocytes and compared their sensitivity to insulin treatments. Results In this study, treatment of T2DM mice with young, undamaged, and ultrapure recombinant mouse serum albumin (rMSA) increased their serum albumin levels, which resulted in a reversal of the disease including reduced fasting blood glucose levels, improved glucose tolerance, increased glucose-stimulated insulin secretion, and alleviated islet atrophy. At the cellular level, rMSA improved glucose uptake and glycolysis in hepatocytes. Mechanistically, rMSA reduced the binding between CAV1 and EGFR to increase EGFR activation leading to PI3K-AKT activation. Furthermore, rMSA extracellularly reduced the rate of fatty acid uptake by islet β-cells, which relieved the accumulation of intracellular ceramide, endoplasmic reticulum stress, and apoptosis. This study provided the first clear demonstration that injections of rMSA can alleviate T2DM in mice. Conclusion Our study demonstrates that increasing serum albumin levels can promote glucose homeostasis and protect islet β cells, which alleviates T2DM.